Phylogenetic affinities of Monarea Szépligeti, 1904 (Hymenoptera: Braconidae, Doryctinae, with description of a new species from Mexico - Belokobylskij, Sergey A.; Zaldívar-Riverón, Alejandro; Coronado-Blanco, Juana M. (Zootaxa, 2014)
The genus Monarea Szépligeti is recorded from Mexico for the first time. A new species, Monarea fridae sp. nov., is described and illustrated from the states of Morelos, Puebla and Jalisco, Mexico. The phylogenetic placement of the genus is investigated based on nuclear (28S) and mitochondrial (COI) DNA sequence data. Based on the relationships recovered, Monarea is transferred to the tribe Holcobraconini, which is also supported by features of the internal ovipositor structure and the venom glands and reservoir. A key to the four currently recognised species of Monarea is provided.